Simultaneous Determination of Diclofenac Sodium and Chlorzoxazone from Combined Dosage Forms by Absorbance Difference Method - Jaleel Saheb, D.; Vijay Bhaskar Reddy, Y.; Chakravarthy, I.E. (Asian Journal of Chemistry, 2016)
A new spectrophotometric method for the simultaneous and separate estimation of diclofenac sodium and chlorzoxazone in binary tablet formulations has been described. The method is based on the estimation of one drug in presence of another drug by absorbance difference method. The diclofenac sodium and chlorzoxazone solutions were scanned over the range of 210 to 304 nm. In this method, two wavelengths 264 and 288 nm were selected for diclofenac sodium at these wavelengths the absorbance difference was almost zero and in case of chlorzoxazone there should be considerable absorbance difference. Similarly the two wavelengths 252 and 294 nm were selected for chlorzoxazone; at these two wavelengths absorbance difference was almost zero and there should be considerable absorbance difference in case of diclofenac sodium. In the mixture of diclofenac sodium and chlorzoxazone solution the absorbance values of the four wavelengths 252, 294, 264 and 288 nm were measured. The amount of diclofenac sodium is directly proportional to the absorbance difference between 252 and 294 nm. Similarly the amount of chlorzoxazone is directly proportional to the absorbance difference between 264 and 288 nm.